1977
DOI: 10.1063/1.323374
|View full text |Cite
|
Sign up to set email alerts
|

Emission probability of hot electrons from silicon into silicon dioxide

Abstract: An experimental method is described for directly measuring the probability of electron emission from the silicon substrate into the SiO2 layer after the electron has fallen through a certain potential drop in traversing the depletion layer and reached the Si-SiO2 interface. The method is based on optically induced hot-electron injection in polysilicon-SiO2-silicon field-effect-transistor structures of reentrant geometry. The emission probability was studied as a function of substrate doping profile, substrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
1

Year Published

1985
1985
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 275 publications
(54 citation statements)
references
References 19 publications
2
51
0
1
Order By: Relevance
“…The structure suggested in [6] has been simulated, with a 2 µm gate length and 42.8 nm oxide thickness, and with the channel-doping profile defined as "15-12-8" in [6]. A first example of the results given by the solver is reported in figure 1, where the distribution function f 0 at a cross-section in the middle of the channel is shown.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…The structure suggested in [6] has been simulated, with a 2 µm gate length and 42.8 nm oxide thickness, and with the channel-doping profile defined as "15-12-8" in [6]. A first example of the results given by the solver is reported in figure 1, where the distribution function f 0 at a cross-section in the middle of the channel is shown.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…On the basis of the lucky-electron model, it can be shown that the fraction of the channel carrier supply which is injected into the gate o xide is given by [129] : . As the substrate current is generated due to impact ionization in the lateral electric field close to the drain, it is linearly proportional to the drain current.…”
Section: Hot Carrier In Jection Cu Rrentsmentioning
confidence: 99%
“…This formalism transforms the initial integro-differential Boltzmann Transport equation into a 2nd order differential equation. The model, based on the results in [19], uses a single isotropic non-parabolic band-structure and includes acoustic and optical phonon scatterings, as well as impact ionization scattering, which have been adjusted to reproduce the Ning's experiment [20].…”
Section: Models' Descriptionmentioning
confidence: 99%